Problems Facing Disabled People in Malawi: A Critical Reflection on My Encounter with a Disabled Woman in a Rural Area in Malawi - Tembo, Memory J. (Journal of Comparative Social Work, 2014)
This critical reflection is based on my encounter with a disabled woman in a district in Malawi, and how I have reflected and analyzed the encounter using social work theories. The essay reflects on the story of the disabled woman and my own perception at that time, in addition to my analysis of these perceptions using different perspectives in social work based on my current understanding of these perspectives. In line with Fook’s (2002; 68) critical reflection techniques, social work theories will be applied to deconstruct and reconstruct the critical incident. The essay highlights the challenges and dilemmas I encountered in attempting to make meaning out of this encounter, which left me helpless and powerless, as I could not offer her any sustainable help at the time.